Terror and Terrorism (I): The Path of History from Sicarii Zealots to Sons of Liberty - Obakhedo, Neville Onebamhoi; Igbinovia, Daisy O. (NIU Journal of Social Sciences, 2020)
With the benefit of hindsight, the phenomenon of terrorism is as old as mankind and its history can be traced to all known human civilizations and economic societies depending on oneâ€™s perspective of the origin of man and civilization or oneâ€™s sense of economic history.  It is instructive to note that the history of terrorism is a history of the various manifestations, and dimensions of the phenomenon including the various types of terrorism and the groups involved, over time, whether state or non-state actors. Even though a lot have been written about the history of terrorism, there seems to be a knowledge gap in the literature on the path of history of terrorism. To this end, this paper captures the essence of the roots and historical trajectory of terrorism with particular emphasis from Sicarii Zealots to Sons of Liberty. The method of gathering information for this paper is the secondary data gathering method through the use of existing literature and the internet. The objective of the paper is for us to have a knowledge-based historical understanding of the genealogy of terrorism across centuries. It is hoped that the robust knowledge of this history of terrorism would provide us with the intellectual foundation for understanding current levels and dimensions of terrorism and guide us in proffering the needed solutions to this phenomenon that is daily widening in scope and intensity and threatening man kind with annihilation. Keywords: History; Terror; Terrorism; Terrorists